PERANAN LEMBAGA KEUANGAN NON BANK DALAM MEMBERIKAN DIVIDEN ATAU KEUNTUNGAN BAGI MASYARAKAT - M syahputra sinaga; Imsar imsar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Non-Bank Financial Institutions (LKBB) Non-Bank Financial Institutions or often referred to as LKBB are organizations engaged in the financial sector whose task is to collect and distribute money to the wider community.This type of research involves field research, which is descriptive qualitative in nature. It involves a research process that produces descriptive data in the form of written narratives from relevant individuals that can be seen in real life. The main objective of non-bank financial institutions is to help entrepreneurs collect financing. LKBB partners offer different credit facilities, both short term and long term. Some individuals believe that bank financial institutions offer more access opportunities than non-bank financial companies. Therefore, honest and fair policies are needed so that individuals can easily get involved in society and understand how non-bank financial institutions work.